The role of type I IFN in autoimmune and autoinflammatory diseases with CNS involvement - Raftopoulou, Sylvia; Rapti, Anna; Karathanasis, Dimitris; Evangelopoulos, Maria Eleftheria; Mavragani, Clio P. (Frontiers in Neurology, 2022)
Type I interferons (IFNs) are major mediators of innate immunity, with well-known antiviral, antiproliferative and immunomodulatory properties. A growing body of evidence suggests the involvement of type I IFNs in the pathogenesis of central nervous system (CNS) manifestations in the setting of chronic autoimmune and autoinflammatory disorders, while IFN-β has been for years, a well-established therapeutic modality for multiple sclerosis (MS). In the present review, we summarise the current evidence on the mechanisms of type I IFN production by CNS cellular populations as well as its local effects on the CNS. Additionally, the beneficial effects of IFN-β in the pathophysiology of MS are discussed, along with the contributory role of type I IFNs in the pathogenesis of neuropsychiatric lupus erythematosus and type I interferonopathies.